Structural properties and gene-silencing activity of chemically modified DNA–RNA hybrids with parallel orientation. Issue 4 (24th January 2018) - Habibian, Maryam; Yahyaee-Anzahaee, Maryam; Lucic, Matije; Moroz, Elena; Martín-Pintado, Nerea; Di Giovanni, Logan Dante; Leroux, Jean-Christophe; Hall, Jonathan; González, Carlos; Damha, Masad J
Abstract: We report, herein, a new class of RNAi trigger molecules based on the unconventional parallel hybridization of two oligonucleotide chains. We have prepared and studied several parallel stranded ( ps ) duplexes, in which the parallel orientation is achieved through incorporation of isoguanine and isocytosine to form reverse Watson-Crick base pairs in ps -DNA:DNA, ps -DNA:RNA, ps -(DNA-2′F-ANA):RNA, and ps -DNA:2′F-RNA duplexes. The formation of these duplexes was confirmed by UV melting experiments, FRET and CD studies. In addition, NMR structural studies were conducted on a ps -DNA:RNA hybrid for the first time. Finally, we provide evidence for the unprecedented finding that ps -DNA:RNA and ps -DNA:2′F-RNA hybrids can engage the RNAi pathway to silence gene expression in vitro .